« Rapid-Onset Gender Dysphoria » - Florence Ashley (Glad!, 2022)
The term ‘rapid-onset gender dysphoria’ (ROGD) was coined in 2016 to describe an alleged epidemic of youth coming out as trans ‘out of the blue’ due to social contagion and mental illness. The term reflects a deliberate attempt to weaponise scientific-sounding language to dismiss mounting empirical evidence of the benefits of transition. This article offers an introduction to the theory of ROGD and its history, presents a detailed critique of the empirical and theoretical claims associated with the theory, and highlights structural concerns with the ROGD discourse. The article argues that claims associated with ROGD, including assertions of declining mental health and degrading familial relationships following coming out, are best explained by the leading ROGD study’s recruitment of parents from transantagonistic websites against a background of growing visibility and social acceptance of trans people. ROGD theory is best understood as an attempt to circumvent existing research demonstrating the importance of gender affirmation, relying on scientific-sounding language to achieve respectability.